Strategi Guru Dalam Mengatasi Miskonsepsi Pembelajaran PAI Kelas 2 SDUT Bumi Kartini Jepara - Jannah, Takhiqul; Rohman, Fathur; Al Mufti, Alex Yusron (UMSU, 2024)
This study aims to identify and analyze the strategies employed by teachers to address misconceptions in Islamic Education (PAI) learning for Grade 2 students at the Integrated Superior Elementary School (SDUT) Bumi Kartini Jepara. Misconceptions in PAI often arise due to students' limited understanding of fundamental topics such as the pillars of Islam, pillars of faith, and core Islamic values, which can hinder the learning process and comprehension of religious concepts. The research adopts a qualitative descriptive methodology, collecting data through document analysis, teacher and student interviews, and classroom observations. This approach aims to gain a comprehensive understanding of how teachers design and implement effective teaching techniques to eliminate students' misunderstandings. The findings reveal that teachers at SDUT Bumi Kartini employs four strategies: contextual learning with educational games, repetitive practice using audiovisual media, storytelling with projector-based digital media, and hands-on activities through creative projects. These strategies have proven effective in correcting misconceptions and improving students' understanding of religious concepts. The study highlights the importance of innovation in PAI teaching, particularly in addressing misconceptions commonly found in primary education. It emphasizes the need for educators to continuously develop adaptive and relevant teaching strategies. In conclusion, effective teacher strategies in overcoming misconceptions in PAI learning for Grade 2 students at SDUT Bumi Kartini Jepara involves interactive methods using digital media and the teacher's active role as a facilitator with a contextual approach to enhance students' understanding.